Constructing the Meaning of Gender Equality, Disability, and Social Inclusion in Indonesian EFL Textbooks - Yuliana Dg. Macora; Novalita Fransisca Tungka; Rini Pakaya; Andi Tendri Jelly (Anaphora : Journal of Language, Literary, and Cultural Studies, 2026)
This study examines the construction of Gender Equality, Disability, and Social Inclusion (GEDSI) within Indonesian EFL textbooks developed under the Kurikulum Merdeka. As social artifacts, textbooks function not only as language learning tools but also as carriers of ideological and social values through complex multimodal systems. This research aims to bridge the gap between pedagogical functionality of visuals or illustrations and the identity analysis of male and female disproportions and the lack of the representational patterns of GEDSI and identify the systemic factors influencing inclusivity in EFL materials. Using a qualitative descriptive design grounded in Social Semiotics, the study analyzed three digital textbooks published in 2022, triangulated with twenty-five stakeholders through focus group discussions (FGDs), including preservice teachers, practitioners, and NGO representatives. Data were processed using NVivo and interpreted through Multimodal Critical Discourse Analysis (MCDA), specifically applying Kress and van Leeuwen’s visual grammar. The findings reveal that while the textbooks have initiated the integration of GEDSI principles, the representation remains uneven; male and able-bodied characters still dominate visually salient and agentive roles, while disability often remains at a symbolic or "tokenistic" level. Furthermore, stakeholders highlighted a significant gap in inclusive aesthetic standards within the illustration process as a barrier to authentic representation. The study highlights a "dilution of inclusivity" as educational levels increase, suggesting that future iterations require a more intentional positioning of minority groups. These results offer both theoretical contributions to multimodal discourse studies and practical insights for textbook developers in creating more equitable and justice-oriented learning resources, such as embedding minority characters into active conversational roles and pairing inclusive visuals with empowering texts, and for teachers to create a learning atmosphere where students can be trained to critically evaluate the surface-level diversity in the textbooks that often undermine the positioning of minority groups.